2023
DOI: 10.1002/brb3.3258
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cognitive function in patients with Huntington's disease from China: A cross‐sectional clinical study

Yang‐Fan Cheng,
Kun‐Cheng Liu,
Tian‐Mi Yang
et al.

Abstract: Background and aimHuntington's disease (HD) is an autosomal dominant inherited neurodegenerative disorder caused by CAG repeats expansion. Cognitive decline contributes to the loss of daily activity in manifest HD. We aimed to examine the cognition status in a Chinese HD cohort and explore factors influencing the diverse cognitive domains.MethodsA total of 205 participants were recruited in the study with the assessment by neuropsychological batteries, including the mini–mental state examination (MMSE), Stroop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In this study, 92 individuals with gene-confirmed HD were recruited between March 2009 and November 2023 in the Department of Neurology at West China Hospital of Sichuan University (Chengdu, China). The participants in this study were from the same cohort as the previous study ( 3 , 26 ). The study received approval from the Institutional Ethics Committee of West China Hospital, Sichuan University, China.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 92 individuals with gene-confirmed HD were recruited between March 2009 and November 2023 in the Department of Neurology at West China Hospital of Sichuan University (Chengdu, China). The participants in this study were from the same cohort as the previous study ( 3 , 26 ). The study received approval from the Institutional Ethics Committee of West China Hospital, Sichuan University, China.…”
Section: Methodsmentioning
confidence: 99%